Research of tax stimulation of the small business in the industry - Григораш, Ольга Вікторівна (Technology audit and production reserves, 2016)
It has been analyzed the statistical reporting data regarding development of the small industrial business. It has been found that the time series results were not true in 2006 and 2012. The article gives coverage of the rapid increase in the dynamics of the volume of industrial products of small businesses with a slight increase in the number of small industrial businesses. The use of regression analysis and correction factor allowed to smooth out the dynamics of statistical data of the sales volume of industrial production of small businesses and reflect the real picture of the small business in the industry development. It has been found the strong inverse relationship between the rate of income tax and the volume of industrial production. There have been calculated the predicted values of small business industrial production volume by using the special income tax rates.